Intraplaque Expression of C-Reactive Protein Predicts Cardiovascular Events in Patients with Severe Atherosclerotic Carotid Artery Stenosis - Aldo Bonaventura; François Mach; Aline Roth; Sébastien Lenglet; Fabienne Burger; Karim J. Brandt; Aldo Pende; Maria Bertolotto; Giovanni Spinella; Bianca Pane; Domenico Palombo; Franco Dallegri; et al. (Hindawi Limited, 2016)
Serum c-reactive protein (CRP) was suggested for the assessment of intermediate cardiovascular (CV) risk. Here, systemic or intraplaque CRP levels were investigated as predictors of major adverse cardiovascular events (MACEs) in patients with severe carotid stenosis. CRP levels were assessed in the serum and within different portions (upstream and downstream) of carotid plaques of 217 patients undergoing endarterectomy. The association between CRP and intraplaque lipids, collagen, neutrophils, smooth muscle cells (SMC), and macrophage subsets was determined. No correlation between serum CRP and intraplaque biomarkers was observed. In upstream portions, CRP content was directly correlated with intraplaque neutrophils, total macrophages, and M1 macrophages and inversely correlated with SMC content. In downstream portions, intraplaque CRP correlated with M1 and M2 macrophages. According to the cut-off point (CRP > 2.9%) identified by ROC analysis in upstream portions, Kaplan-Meier analysis showed that patients with high CRP levels had a greater rate of MACEs. This risk of MACEs increased independently of age, male gender, serum CRP, and statin use. In conclusion, in patients with severe carotid artery stenosis, high CRP levels within upstream portions of carotid plaques directly and positively correlate with intraplaque inflammatory cells and predict MACEs at an 18-month follow-up period.